GIMAP8 could serve as a potential prognostic factor for lung adenocarcinoma and is closely related to immunity - Xinfeng Wei; Wei Wei; Hongmei Liu; Junxuan Yi; Mingwei Wang; Weiqiang Xu; Mingqi Zhao; Mengdie Zhao; Rong Wang; Shunzi Jin (Scientific Reports)
Abstract GTPase IMAP family member 8 (GIMAP8) plays a key role in pathophysiology of several malignancies. The objective of this current research endeavor was to investigate the prognosis value of GIMAP8 in lung adenocarcinoma and examine how it relates to immunity. Expression profiles associated with GIMAP8 and related clinical details were acquired from The Cancer Genome Atlas database, and we conducted survival analysis, enrichment analysis and immune infiltration studies. Additionally, we evaluated the effect of GIMAP8 on radiation resistance of tumor by in vivo and in vitro experiments. Our results showed that lung adenocarcinoma tumor tissues exhibited lower GIMAP8 levels compared to nearby normal tissues. Furthermore, decreased GIMAP8 expression strongly correlated with poorer OS. The expression of GIMAP8 is closely related to the formation of radiation resistance in tumor cells. GSEA identified multiple signaling pathways linked to GIMAP8, including immune-related, chemokine, cell adhesion molecule, and NF-κB signaling pathways. GIMAP8 expression strongly correlated with the expression of immune checkpoint molecules, tumor mutational burden, tumor neoantigen burden, immune cells, and tumor immune microenvironment. GIMAP8 was found to have an inhibitory effect on lung adenocarcinoma and was closely related to the immune response. Moreover, GIMAP8 may also influence radiation resistance in tumors.